Role of Social media marketing to enhance the supply chain and business management - Kundharu Saddhono; Gumgum Gumelar; Aswin Aswin; Nasrul Nasrul; Firmansyah Y. Alfian; Syamsiah Badruddin; Niken Paramitasari; Ramlan Siregar; Paisal Halim (International Journal of Supply Chain Management, 2020)
Abstract— Combining the social interaction and technology social media provide a low cost tool. Many companies are leveraging more robust social platforms to better plan and control their supply chain. The purpose of this article is to provide researches of the supply chain management a reference with the main concepts of social media: Twitter, Flickr, Instagram, YouTube, Facebook, Viber, and Google +, Pinterest etc. Drawing on social capital theory, this study uses a sentiment analysis approach to investigate the impact  of  social  media  usage by supply  chain  partners  on  supply  chain  performance. With the help of social media it is very easy to interact with customer and other people and it can make the community of the customers. It is possible assemble a network of clients where it can draw in them with quality substance and these stages additionally enable to present the product. With the help of the social media it provides an approach to contacts with companions, Potential customers and clients. It customizes the "brand" and makes it possible to spread the content in colloquial ways, however supply chain managers to adjust their supply chain strategies to have a sustainable competitive advantage